1976
DOI: 10.1002/art.1780190603
|View full text |Cite
|
Sign up to set email alerts
|

The lupus anticoagulant

Abstract: The clinical and laboratory experience with the lupus anticoagulant was reviewed in 37 patients. The anticoagulant is thought to act by blocking the activation of prothrombin by the prothrombin activator complex of factors Xa, V, and phospholipid. Although the anticoagulant has been principally associated with diseases of immune origin, 14 of the present patients had disorders not thought to be immune in nature. Eighteen patients underwent twenty-one operative procedures with only a single episode of excessive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…To our knowledge, this association has not been reported before in prospective studies although sporadic cases associating LLA with uremia or renal impairment has been previously described [14,[29][30][31]. LLA was first described in SLE, although only a small proportion of patients with this anticoagulant is now found to have SLE.…”
Section: Discussionmentioning
confidence: 80%
“…To our knowledge, this association has not been reported before in prospective studies although sporadic cases associating LLA with uremia or renal impairment has been previously described [14,[29][30][31]. LLA was first described in SLE, although only a small proportion of patients with this anticoagulant is now found to have SLE.…”
Section: Discussionmentioning
confidence: 80%
“…Lupus anticoagulant is thought to occur rarely in nor mal subjects [9,10,17], The original report of Nilsson et al [12] associating intrauterine death with lupus antico agulant has been followed by reports of unsuccessful pregnancies in patients possessing this antibody [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The initial report of lupus anticoagulant involved hemorrhage [2], but bleeding complications have gener ally involved concomitant platelet dysfunction, throm bocytopenia, or hypoprothrombinemia [4], Retro spective [5] and prospective [6] studies have indicated an undue incidence of thromboembolism in patients with lupus anticoagulant. Recurrent TIA involving var ious arterial territories in young adults who had no angiographic evidence of occlusive cerebrovascular dis ease were reported by Landi et al [7], while multiple strokes accompanied lupus anticoagulant in a young woman with Degos' disease described by Englert et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…It was first described in patients with systemic lupus ery thematosus (SLE) [2], but has subsequently been associ ated with malignancy and inflammatory disorder, and occurred without any underlying disease [3]. Despite this prolongation of bleeding indices, hemorrhagic complica tions are infrequent [4], A tendency to thromboembo lism has instead been encountered [5,6], Cerebral thrombotic events have been increasingly recognized [7][8][9]. Transient ischemic attacks (TIA) [7] and large-vessel thrombotic infarctions [8-10] have been described, but lacunar infarctions have not heretofore been reported.…”
mentioning
confidence: 99%